Design, synthesis and preliminary biological evaluation of indoline-2, 3-dione derivatives as novel HDAC inhibitors. Issue 15 (1st August 2015) - Jin, Kang; Li, Shanshan; Li, Xiaoguang; Zhang, Jian; Xu, Wenfang; Li, Xuechen
Graphical abstract: Abstract: Histone deacetylases (HDACs) are zinc-dependent or NAD + dependent enzymes and play a critical role in the process of tumor development. Herein a series of indoline-2, 3-dione derivatives have been designed and synthesized as potential HDACs inhibitors. The preliminary biological evaluation showed that most compounds synthesized have exhibited moderate Hela cell nuclear extract inhibitory activities, among which compound 25a (IC50 = 10.13 nM) has shown the best efficacy. The anti-proliferative activities of some of these compounds were also discussed.